Editorial Enletawa Journal 11.1 - Romero Archila, Yuranny Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Research and reflection are key concepts in education. Regarding reflection, Korthagen (2001, p. 53) states that “reflection is the instrument by which experiences are translated into dynamic knowledge” when we reflect or read others’ reflections, we are constantly transforming knowledge. The current issue of ENLETAWA JOURNAL contains different research reports and reflections that will encourage the readers to start or continue different research studies and reflections.